1) ![y^4-81=(y^2-9)(y^2+9)=(y-3)(y+3)(y^2+9) y^4-81=(y^2-9)(y^2+9)=(y-3)(y+3)(y^2+9)](https://tex.z-dn.net/?f=y%5E4-81%3D%28y%5E2-9%29%28y%5E2%2B9%29%3D%28y-3%29%28y%2B3%29%28y%5E2%2B9%29)
2)
x_1=2; x_2=-3;" alt="(x-2)(2x+6)=0 => x_1=2; x_2=-3;" align="absmiddle" class="latex-formula">
3)
x(x^2-9)=x(x-3)(x+3) " alt=" x^3-9x=0 => x(x^2-9)=x(x-3)(x+3) " align="absmiddle" class="latex-formula">
x_1=0; x_2=3; x_3=-3" alt="=> x_1=0; x_2=3; x_3=-3" align="absmiddle" class="latex-formula">
4) ![\frac{4a^2 -4a+1}{4a^2-1}=\frac{(2a-1)(2a-1)}{(2a-1)(2a+1)}=\frac{(2a-1)}{(2a+1)} \frac{4a^2 -4a+1}{4a^2-1}=\frac{(2a-1)(2a-1)}{(2a-1)(2a+1)}=\frac{(2a-1)}{(2a+1)}](https://tex.z-dn.net/?f=%5Cfrac%7B4a%5E2+-4a%2B1%7D%7B4a%5E2-1%7D%3D%5Cfrac%7B%282a-1%29%282a-1%29%7D%7B%282a-1%29%282a%2B1%29%7D%3D%5Cfrac%7B%282a-1%29%7D%7B%282a%2B1%29%7D)